Exploring student engagement as a nexus for integrating theory and practice in language teacher education - Bendtsen, Marina; Forsman, Liselott (System (Linköping), 2025)
Action research (AR) has been suggested as a tool in teacher education for bridging the theory–practice gap. This study, set in Finland, explores how the theoretical framework of student engagement integrated into small-scale AR-based projects can be used to strengthen the nexus between theory and practice in language teacher education. Five student teachers partook in the study. Data consist of tasks connected to student engagement included in their study programme: initial teacher profiles, written reflections from their teaching practice, a project plan and poster based on their small-scale AR project, and a final group discussion. Findings are reported through narrative analysis. The findings show that the AR projects provided valuable opportunities for applying the theoretical framework of student engagement in practice, while also furthering the student teachers' understanding of the concept. Additionally, the benefits of repeatedly including the framework in connection to various tasks throughout the 20-week semester proved to be an important scaffold. This consistency in combination with a coherence between the university and practice school settings provided additional scaffolding. Challenges in relation to student teachers’ ability to apply the theoretical framework seemed connected to their current level of development on their journey to becoming teachers.